Axial muscle size quantification by cardiac mri as a strong predictor of major cv events in hf. (25th November 2020) - Lopes Da Cunha, G.J; Rocha, B.M.L; Freitas, P.N; Lopes, P.M.D; Guerreiro, S; Andrade, M.J; Aguiar, C.M.T; Abecasis, J; Saraiva, C; Mendes, M; Ferreira, A
Abstract: Background: Clinical overt cardiac cachexia is a late and ominous sign in patients with heart failure (HF) and reduced left ventricular ejection fraction (LVEF). Low muscle mass could serve as a surrogate of subclinical cardiac cachexia and has already been shown to predict major adverse events in HF patients. The main goal of this study was to assess the feasibility and prognostic significance of a simplified muscle mass quantification by cardiac magnetic resonance (CMR) in HF with reduced LVEF. Methods: HF patients with LVEF <40% referred for a clinically indicated CMR (1.5T scanner) were retrospectively identified in a single center. The main exclusion criteria were known primary muscle disease, diagnosed or suspected infiltrative myocardial disease and implanted device. The area of both pectoralis major muscles was measured on standard axial images at the level of the carina using manual outlining. To account for the effect of age and gender, pectoralis major muscle area was expressed as the difference in standard deviations in relation to the mean pectoralis major muscle area of a healthy cohort of 32 females and 37 males aged between 50 and 80 years old. The primary endpoint was a composite of all-cause mortality or HF hospitalization. Survival analysis was performed with Cox-regression hazards model and Kaplan-Meier. Results: A total of 184 HF patients were included (mean age 65±12 years; 78% male; LVEF 30±8%). Lower pectoralis major area was significantly correlated with older age (r=−0.36, p<0.001), lower LVEF (r=0.14, p=0.050) and higher NT-proBNP (r=−0.44, p<0.001). During a median follow-up of 22 months (IQR: 14–29) there were 44 (23.9%) patients who met the primary endpoint (a total of 15 patients died and 29 had at least one HF hospitalization). In multivariate analysis, LVEF (HR per 1%: 0.95; CI: 0.91–0.98; p=0.004), creatinine (HR per 1mg/dL: 2.12; CI: 1.09–4.11; p=0.026) and pectoralis major area (HR per 1 SD below the mean: 1.40; CI: 1.01–1-1.95; p=0.047) were independent primary endpoint predictors. Conclusions: Pectoralis major size measured by CMR in HFrEF was independently associated with a higher risk of death or HF hospitalization. Further studies need to be undertaken to establish appropriate age and gender-adjusted cut-offs of muscle areas that identify high-risk subgroups. Funding Acknowledgement: Type of funding source: None